Hybrid procedures for persistent atrial fibrillation: necessity and timing of the catheter ablation stage - Bulava, Alan (Journal of Thoracic Disease, 2017)
In our recent paper (1) we tried to identify predictors of arrhythmia recurrence in patients undergoing a hybrid ablation procedure consisting of both an epicardial and endocardial radiofrequency (RF) ablation, performed in a delayed sequential manner, in patients with persistent atrial fibrillation (AF), with the majority presenting with long-standing persistent arrhythmia (87%). By design, our cohort of patients consisted of one of the “less curable” forms of arrhythmia, especially if treated using only conventional catheter ablation techniques. The majority of our patients might very well have been precluded from receiving invasive therapy if they had been assessed just for a catheter ablation, particularly in less experienced centers.